2017
DOI: 10.1371/journal.pone.0175398
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic protection of a living and dead Lactobacillus strain against aluminum-induced brain and liver injuries in C57BL/6 mice

Abstract: Our previous study found that Lactobacillus plantarum CCFM639 had the ability to alleviate acute aluminum (Al) toxicity when the strain was introduced simultaneously with Al exposure. This research was designed to elucidate the therapeutic effects of living and dead L. plantarum CCFM639 against chronic Al toxicity and to gain insight into the protection modes of this strain. Animals were assigned into control, Al only, Al + living CCFM639, and Al + dead CCFM639 groups. The Al exposure model was established by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
8
0
5
Order By: Relevance
“…However, supplementation with CAU 1447 or CAU 1447 cream cheese significantly prevented the increases in serum ALP, AST, and ALT levels caused by alcohol consumption. These results are supported by several previous studies demonstrating that treatment with some probiotics containing Lactobacillus spp., such as Lactobacillus brevis and Lactobacillus casei, and Bifidobacteria suppressed the upregulation of biomarkers or inflammatory factors related to alcoholic liver injury in patients and animal models (Segawa et al, 2008;Stadlbauer et al, 2008;Tian et al, 2017). Therefore, our results demonstrated decreases in ALP, AST, and ALT levels following supplementation with CAU 1447 or CAU 1447 cream cheese.…”
Section: Discussionmentioning
confidence: 50%
“…However, supplementation with CAU 1447 or CAU 1447 cream cheese significantly prevented the increases in serum ALP, AST, and ALT levels caused by alcohol consumption. These results are supported by several previous studies demonstrating that treatment with some probiotics containing Lactobacillus spp., such as Lactobacillus brevis and Lactobacillus casei, and Bifidobacteria suppressed the upregulation of biomarkers or inflammatory factors related to alcoholic liver injury in patients and animal models (Segawa et al, 2008;Stadlbauer et al, 2008;Tian et al, 2017). Therefore, our results demonstrated decreases in ALP, AST, and ALT levels following supplementation with CAU 1447 or CAU 1447 cream cheese.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies have reported the beneficial protection of L. plantarum on stress-induced behavior dysfunction. Administration of living or dead L. plantarum improved cognitive deficits against aluminum-induced brain and liver injuries in mice [33] and attenuated anxiety behavior of stressed zebrafish [34]. Administration of L. plantarum MTCC 9510 reduced oxidative stress markers and inflammatory cytokines in the brain and serum and improved stress-induced behavioral despair [35].…”
Section: Introductionmentioning
confidence: 99%
“…brevis, were able to bind and remove toxic metals (Yu et al 2016). A recent study by Tian et al (2017) also suggests the potential of the Lb. plantarum strain to alleviate the aluminium-induced brain injuries in mice.…”
Section: Influence Of Lb Brevis Sf9b and Lb Plantarum Sf9c On Gut Mmentioning
confidence: 88%